Perception of online teacher self-efficacy: A multi-state study of nursing faculty pivoting courses during COVID 19. (November 2021) - Culp-Roche, Amanda; Hardin-Fanning, Fran; Tartavoulle, Todd; Hampton, Debra; Hensley, Angie; Wilson, Jessica L.; Wiggins, Amanda Thaxton
Abstract: Background: COVID-19 forced many colleges and schools of nursing to abruptly pivot face-to-face learning to online formats. Online teaching is not new, but some faculty have not taught in a virtual environment and rapidly transitioning courses online was challenging. It is not known if teacher self-efficacy was impacted by these circumstances. Objectives: We aimed to assess online teacher self-efficacy of nursing faculty who transitioned at least one-face-to face course to an online format. We hypothesized that faculty with previous online teaching experience and greater self-rated instructional support would demonstrate higher online teacher self-efficacy scores compared to faculty who had little or no online teaching experience or reported less satisfaction with instructional support. Design: A cross-sectional, descriptive design was used. Setting: Faculty from ten universities across the United States were recruited. Participants: Nursing faculty ( N = 84) who transitioned at least one face-to-face course to an online format during COVID-19 were included in the study. Methods: Participants completed the 32-item Michigan Nurse Educators Sense of Efficacy for Online Teaching (MNESEOT) instrument and a demographic questionnaire which included items about prior online teaching experience and instructional support. Results: Participants scored overall teacher self-efficacy high (75th percentile). "Computer skills" were scored highest while "student engagement" scored lowest. Prior online teaching was a predictor of higher online teacher self-efficacy; however, instructional support was not a predictor of higher online teacher self-efficacy. Conclusion: Nursing faculty reported a high level of online teacher self-efficacy during an abrupt pivot from face-to-face teaching to a virtual format. Pre-emptive opportunities to teach online can build self-efficacy for novice faculty. Faculty and students will benefit from improving student engagement skills, especially during isolating and overwhelming events such as the COVID-19 pandemic.